2018
DOI: 10.1002/2017wr022012
|View full text |Cite
|
Sign up to set email alerts
|

Regional Variability of Nitrate Fluxes in the Unsaturated Zone and Groundwater, Wisconsin, USA

Abstract: Process‐based modeling of regional NO3– fluxes to groundwater is critical for understanding and managing water quality, but the complexity of NO3– reactive transport processes makes implementation a challenge. This study introduces a regional vertical flux method (VFM) for efficient estimation of reactive transport of NO3– in the vadose zone and groundwater. The regional VFM was applied to 443 well samples in central‐eastern Wisconsin. Chemical measurements included O2, NO3–, N2 from denitrification, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 123 publications
1
28
0
Order By: Relevance
“…The second point is further suggested by a significant increase in planted corn area, yet significant decrease in estimated fertilizer application in Scotts Bluff County. In other words, it is possible other variables beyond irrigation practice and canal management are currently driving the decreasing trends in groundwater [NO 3 − ], consistent with other studies that emphasize the need to improve both water and nitrogen management in agricultural production [12,13,70,71]. It should be noted, however, that, while this study was unable to detect a significant reduction in recharge rates, limitations and uncertainties associated with groundwater age-dating and recharge calculations may make it difficult to identify a small but meaningful decrease.…”
Section: Further Discussionsupporting
confidence: 77%
“…The second point is further suggested by a significant increase in planted corn area, yet significant decrease in estimated fertilizer application in Scotts Bluff County. In other words, it is possible other variables beyond irrigation practice and canal management are currently driving the decreasing trends in groundwater [NO 3 − ], consistent with other studies that emphasize the need to improve both water and nitrogen management in agricultural production [12,13,70,71]. It should be noted, however, that, while this study was unable to detect a significant reduction in recharge rates, limitations and uncertainties associated with groundwater age-dating and recharge calculations may make it difficult to identify a small but meaningful decrease.…”
Section: Further Discussionsupporting
confidence: 77%
“…Previous studies have suggested different types of nitrate budget quantification at a regional scale, which include the transient nature of nitrate storage in deep vadose zones (Roelsma & Hendriks, ). Green et al () introduced a mechanics‐based approach to account for reactive nitrate transport in the unsaturated zone at a regional scale. Subsequently, this method was implemented within a statistical framework based on GIS variables to reduce model complexity (Nolan et al, ).…”
Section: Discussion and Future Researchmentioning
confidence: 99%
“…The candidate predictor variables (see Table ) described in Feinstein et al () are intended to span the physical factors that might influence the age of shallow well discharge. They were initially chosen guided by the common analytical equation for mean travel time in the saturated zone from Vogel (), following the symbology of Green et al (): trueτ¯=nsHsRln()HsHsz, where trueτ¯ is the mean travel time, n s is porosity, R is recharge, H s is the saturated thickness of the aquifer, and z is the vertical position within the aquifer.…”
Section: Methodsmentioning
confidence: 99%
“…The candidate predictor variables (see Table 1) described in Feinstein et al (2018) are intended to span the physical factors that might influence the age of shallow well discharge. They were initially chosen guided by the common analytical equation for mean travel time in the saturated zone from Vogel (1967), following the symbology of Green et al (2018…”
Section: Data Used In Metamodelingmentioning
confidence: 99%